Assessment rehabilitation efficiency of patients after acute disorder of cerebral circulation, according to the hospital register - L. A. Koscheeva; D. L. Zhukova; E. L. Berezina; M. V. Ponomareva; A. R. Nikolaeva; A. A. Malkova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
The widespread prevalence of acute cerebrovascular accidents (ACVA) around the world (up to 30 million annually), high disability draw close attention of doctors to the system of care for patients with strokes. Rehabilitation is of great importance in it, the main task of which is to  restore impaired body functions and return patients to a full life. The best way to organize rehabilitation is considered to be an integrated approach with the formation of a multidisciplinary team of doctors. An individual approach to each patient is also important: his age, medical history, social status, relationships with family, lifestyle. Doctors carry out rehabilitation measures to restore the patient's motor, social, household and psychoemotional functions. The results of rehabilitation and restoration of health of people who have suffered a stroke depend on many factors, but to a large extent on a favorable attitude and the persistent desire of the patients themselves to return to health. The aim of the study was, based on the results of studying the case histories of patients with ischemic and hemorrhagic stroke of the neurological department on the basis of the BUZ UR of the First Republican Clinical Hospital of the Ministry of Health of the UR, to assess the effectiveness of rehabilitation of patients who underwent stroke.